Pre-treatment of cellulosic fibres with some chemicals for effective sizing - (:unkn) unknown (My University, 2011)
There are a number of problems experienced during internal sizing of papers. Poor size retention and back water contamination are just two of them. The method which supports the maximum attachment of sizing agents specifically to cellulose fibres is needed to solve some problems encountered with sizing operations. In this work, handsheets were produced from bleached long fibres with the blend of pretreated fibres with various sizing chemicals. The fibre pretreatments were achieved by mixing unbeaten fibres with rosin, paraffin and alkyl ketene dimer (AKD) emulsions at quite higher proportions, followed by filtration and drying. Strongly sized fibres then were beaten and mixed with untreated fibres in making a number of handsheets. Pre-treatments were discussed in respect to paper sizing, recycling and some suggestions were made.
Keywords: Acid-alkali paper; Fibre modification; Paper sizing; Reactive sizing; Recycling